2006
DOI: 10.1111/j.1600-0749.2006.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human skin pigmentation and responses to ultraviolet radiation

Abstract: SummaryPigmentation of human skin is closely involved in protection against environmental stresses, in particular exposure to ultraviolet (UV) radiation. It is well known that darker skin is significantly more resistant to the damaging effects of UV, such as photocarcinogenesis and photoaging, than is lighter skin. Constitutive skin pigmentation depends on the amount of melanin and its distribution in that tissue. Melanin is significantly photoprotective and epidermal cells in darker skin incur less DNA damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
178
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(191 citation statements)
references
References 101 publications
0
178
0
3
Order By: Relevance
“…Darkly pigmented, eumelanin-rich skin protects against considerable damage to DNA caused by UVR [80], and is associated with much lower rates of skin cancer than lightly pigmented skin [81 -84]. The protective effects of eumelanin on DNA structure were established by an experimental study showing that heavily pigmented melanocytes resumed proliferation faster after UVB irradiation than can lightly pigmented ones, and that DNA from lightly pigmented melanocytes was more badly damaged than DNA from heavily pigmented melanocytes after irradiation with increasing doses of UVB [81,85].…”
Section: Diseases Related To Higher Levels Of Uvr Exposure Relative Tmentioning
confidence: 99%
“…Darkly pigmented, eumelanin-rich skin protects against considerable damage to DNA caused by UVR [80], and is associated with much lower rates of skin cancer than lightly pigmented skin [81 -84]. The protective effects of eumelanin on DNA structure were established by an experimental study showing that heavily pigmented melanocytes resumed proliferation faster after UVB irradiation than can lightly pigmented ones, and that DNA from lightly pigmented melanocytes was more badly damaged than DNA from heavily pigmented melanocytes after irradiation with increasing doses of UVB [81,85].…”
Section: Diseases Related To Higher Levels Of Uvr Exposure Relative Tmentioning
confidence: 99%
“…It has been reported that skin pigmentation is regulated by a variety of intrinsic and extrinsic factors [7,8] , as well as diverse signaling pathways including protein kinase A (PKA), phosphatidylinositol 3-kinase (PI3K), and mitogen-activated protein kinases (MAPKs) [9][10][11][12][13] . In particular, the MAPK kinase (MEK)/extracellular signal-regulated kinase (ERK) and the PI3K/Akt pathways have been shown to negatively regulate melanin synthesis in melanocytes and melanoma cells [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Les mélanines sont transmises aux kératinocytes sous forme de petits granules appelés méla-nosomes ( Figure 1B). La pigmentation assure ainsi une protection naturelle du génome kératinocytaire en absorbant les ultraviolets [12]. L'importance de la protection assurée par les mélanines est illustrée par des taux de cancers cutanés significativement plus élevés chez les personnes à peau claire que chez les personnes à peau plus sombre.…”
Section: P53 Et Pigmentationunclassified